Las artes plásticas en el desarrollo de la creatividad en los niños del primer año de Educación Básica de la Unidad Educativa " CEC". - Malla Coronel, Verónica Mariela (2021)
The present research focusing in the theme: "The plastic arts in the development of creativity in the children of the first year of basic education of the Educational Unit "CEC". Therefore, the general objective is to strengthen the development of creativity through the plastic arts in the children of the first year of basic education of the "CEC" Educational Unit. Therefore, in order to carry out the research more effectively, it is important to carry out the specific objectives such as: Identify the types of plastic arts that stimulate the creativity of children, establish the activities of the plastic arts for the creativity of children, elaborate the methodological proposal on the plastic arts in the development of creativity, and finally evaluate the results of the application of the proposal. In order to carry out the research it is necessary to carry out a system of tasks that are consistent with the stated objectives. The methodology used in the research has a quantitative approach, since the deductive method has been used, that is to say, it is based on existing theories to support the dependent and independent variables which are the plastic arts and the development of creativity, in this way through the diagnosis it was possible to verify the reality of the Educational Unit, the proposal that was achieved with this research was to conduct workshops with different grapho-plastic techniques such as dactyl-painting, modeling, free drawing, symmetric drawing, and the development of creativity, modeling, free drawing, symmetry, stamping, thus obtaining favorable results because through the work done in a practical and joint way with parents and teachers of the institution has allowed to strengthen creativity in children through an adequate and timely evolutionary development so that they can express their feelings and emotions in everyday life.